Climate Change and Indian Agriculture: a Review of Evidence and its Implications. - Sah, D.C. and Tomar, Shibhra Singh (2010)
By the mid–twenty-first century, surface temperature in India may increase by 30 to 40C, leading to noticeable variability in the monsoon pattern, decreased number of rainy days, and an increase in flooding and intensity of droughts. This will seriously effect the food grain production, environment and life sustaining ecosystems in India. Policymakers have to assess these adverse implications immediately. The review of available evidence reveals that there are clearly two sets of recommendation emanating from activist and agricultural scientists. Activists argue that India’s food security rests on the monsoon. Monsoon failure and widespread drought implies a deepening of the already severe food crisis triggered by trade liberalization policies which has made India the capital of hunger. Since 1966, as a consequence of the introduction of the Green Revolution model of water intensive chemical farming, India has over-exploited her ground water, creating a water famine. High yielding varieties (HYVs) use about ten times more water than the bio-diverse ecological farming systems. The activists believe that severe drought in India will force the government to act. It is vital that the government does not use this emergency to act as a marketer of GM seeds. On the other hand, the Government of India argues that poor and marginal farmers who own less than one acre of land mostly populate high-risk areas. There is an urgent need to evolve comprehensive climate resilience strategies that must factor in risk assessment, better water management, developing varieties that can do well in stressful conditions, and bringing about certain changes in agricultural practices. The scientists recommend the following: (i) Conservation and large-scale distribution of open pollinated varieties or open source seeds of water prudent crops; (ii) Promotion of organic agriculture to increase climate resilience and food and water security; (iii) Incentives to farmers for a shift from water guzzling Green Revolution agriculture to water conserving bio-diverse organic farming; (iv) New land use systems; (v) Developing new drought resistance varieties of crops; (vi) Increasing the area under watershed and sustainable irrigation; (vii) Adapting agronomic practices to new environments; (viii) Livelihood diversification. While long term ecological security, food security and water security needs these steps, the immediate needs are changing energy use pattern and policy. This calls for a reappraisal of the subsidy to petroleum products and demand side management, legal regime for energy conservation and energy efficient technology, reformulating Indian transport policy, bringing policy for conservation absorption of CO2 by natural process, allocation of funds for adaptation and linking with insurance market.